Physical-chemical quality of salt marketed in the Municipality of Mossoró, Rio Grande do Norte, Brazil (Research, Society and Development, 2020)
Salt is a primary ingredient in human food, but its quality must be evaluated. The objective was to evaluate the physical-chemical quality of table salt marketed in the city of Mossoró, Rio Grande do Norte, Brazil. Six commercial samples of refined table salt and three samples of ground salt from different brands were randomly selected at local supermarkets. The contents of mass, humidity, turbidity, iodine and chlorides in sodium chloride were determined. The mass of the samples was found to be in conformity in most of the analyzed samples. The levels of humidity, turbidity and iodine were above what was allowed by the legislation. The levels of chlorides in sodium chloride were below that required for all refined salts and for the ground salt of sample B. All samples collected are outside the standards of quality of salt for human consumption required by law.